OUTCOMES OF SECOND TRIMESTER SURGICAL ABORTION: THE EXPERIENCE OF A TERTIARY HEALTH FACILITY IN ETHIOPIA - Hurissa, Tesfaye; Bell, Jason; Wondafrash, Mekitie; Surur, Feiruz; MacAfee, Lauren; Dalton, Vanessa; Kahn, Chava; Megan, Yanik (Ethiopian Journal of Reproductive Health, 2019)
ABSTRACT BACkGROUND: Abortion is defined as expulsion or extraction of a fetus before fetal viability. It is a very common occurrence globally (40-50 million per annum. There is increasing evidence to suggest that dilation and evacuation (D&E) leads to fewer complications than medical abortion for second trimester termination of pregnancy. However, there is no recent documentation of the outcome of such a method in Ethiopia. Hence the aim of this study is to document the outcome of second trimester D&E performed at St Paul Hospital and Millennium Medical College (SPHMMC). OBJECTIVE: To describe clinical characteristics and short-term outcomes of second trimester surgical abortion at SPHMMC. METHODS AND SUBJECTS: A retrospective cross-sectional study design was employed to review all cases of dilation and evacuation performed in the six months period from January 1, 2018- July 30, 2018. A structured questionnaire was used to collect selected socio-demographic data, clinical characteristics and acute complications. Data was entered and analyzed using IBM SPSS Statistics, version 20.0 (IBM Corp, Released 2011). RESULT: A total of 43 client records were reviewed and used for this analysis. The median (IQR) age of the study participants was 24 (20,26), with age range of 16 to 34 years old. The average gestational age is 16 weeks + 2 days (ranging from 13 weeks + 1 day to 20 weeks + 6 days). All women received doxycycline prior to performing D&E. No ultrasound was used during all the procedures. Over all complication rate is 2.3%, with 1 case of uterine perforation. The contraceptive uptake rate was 88.4% (38/43). The most common post abortion family planning method was long acting reversible contraceptives (LARC). CONCLUSION: Our review demonstrated that D&E is safe after applying recommended procedures in a tertiary health facility in Ethiopia. Further analysis using a larger sample should be undertaken and comparison should be made with medical induction in order to establish the safety and effectiveness of second trimester surgical abortion. kEY WORDS: second trimester safe abortion, Dilation & Evacuation (Ethiopian Journal of Reproductive Health; 2019; 11;1:1-8)